Peranan Mikroorganisme Pendegradasi Plastik: Tinjauan Biodegradasi Plastik, Mekanismenya, serta Mikroorganisme yang Berperan - Putu Cindy Arista (Pro-Life, 2023)
Plastic is difficult to decompose in nature because it is a synthetic polymer made by humans and is made from petroleum. The problem that arises from the uncontrolled use of plastic is the accumulation of plastic waste in the environment which is not handled properly and becomes a source of environmental pollution. Plastic waste creates various kinds of environmental problems that disturb the balance of ecosystems and have an impact on the life of organisms in the environment. To overcome this problem, it is necessary to carry out related research as an effective solution for dealing with plastic waste. Biodegradation is one of the right methods for dealing with plastic waste now and in the future. However, there is limited review of the bio-decomposition of plastics, the microbial species present, the effectiveness of degradation, and the mechanisms involved. Based on this, this research focuses on a brief review of plastic biodegradation such as the factors that affect biodegradation, the species of microorganisms that play a role in the degradation of macro and micro-plastics, as well as the mechanism of plastic degradation through enzymes from the viewpoint of microorganisms. Various species of microorganisms such as bacteria, algae and fungi have the ability to decompose plastics but they cannot mineralize plastics completely. Meanwhile, research on the enzymes involved in plastic degradation is still limited, especially in the case of algae. This review can be a reference for researchers to find effective strategies to address the problem of plastic waste worldwide.